Do Gendered Social Institutions and Resources Promote Women's Entrepreneurial Intentions? A Multi-Country Study - Jin, Meng (Université d'Ottawa / University of Ottawa, 2014)
Women’s entrepreneurship has garnered substantial research interest over the years. The majority of the previous research investigates nascent entrepreneurship rate, while fewer studies investigate entrepreneurial intentions. This study focuses on the relationship between women's entrepreneurial intentions and institutional and personal variables. This study uses data from Global Entrepreneurship Monitor and Social Institutions and Gender Index databases and covers 43 countries. Both factor analysis and linear regression methodologies are employed. The results show that if women possess higher levels of entrepreneurial skills, have lower levels of fear of failure, and greater social networks, they are more likely to have entrepreneurial intentions. However, the more women have access to land, bank loans, and property other than land, the less likely they desire to become entrepreneurs. Also, social services for women's careers and fair entrepreneurial opportunities for women do not have significant impacts on women's entrepreneurial intentions. The theoretical and empirical implications of the results are discussed.
Keywords: women entrepreneur; entrepreneurial intention; social institutions; gendered resources